Infrastructure as Code Development in Cloud Computing Using Terraform for The Ministry of PUPR Application - Firmansyah Wicaksono; Angga Setiyadi (Universitas Komputer Indonesia, 2024)
Terraform, as one of the Infrastructure as Code (IaC) tools, simplifies consistent and efficient cloud resource development using HashiCorp Configuration Language (HCL), a declarative syntax where each code block defines the resources to be provisioned. This study aims to build Google Cloud Platform services using Terraform and develop a simple web application related to the Ministry of PUPR with CRUD (Create, Read, Update, Delete) functionality, tested and monitored using the DevOps software development method. Docker is utilized as a container platform to package applications, ensuring consistent management from development to production. Additionally, CI/CD (Continuous Integration / Continuous Delivery / Deployment) pipelines are integrated to automate development processes, accelerating application deployment alongside cloud services built with Terraform. The results show that combining Terraform, CI/CD pipelines, and Docker within the Google Cloud Platform ecosystem using DevOps increases efficiency, effectiveness, speed, and consistency in managing cloud infrastructure and application deployment processes